The Suitability of Arabic Language Question Item in the Perspective of Bloom Taxonomy Revision l Tanasub Bunudi As’ilah al-Lughah al-‘Arabiyyah fi Dhaui Tashnif Bloom al-Mu'addal - Qodri, Muhammad; Asrori, Imam; Bahruddin, Uril (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2022)
The content of the items in the Arabic language questions between the language and elements of the skill was not balance. It was based on the linguistic elements or the linguistic skills and the percentage of each levels of knowledge that is not balance. This study aimed to analyze the suitability of UAMBN Arabic language test Question Item for Madrasah Aliyah level with Bloom Taxonomy Revision. Research data was obtained from documentation and interviews. The documents were the Arabic language questions for the national final exam at the stage of the Islamic secondary school in the 2016/2017 academic year. Meanwhile, the interview was conducted with an expert in the evaluation of Arabic language education and the director of curriculum center and the stakeholders of Arabic language question items design. The findings of this study were the question items of Arabic test of UAMBN were suitable with Core Competency and Basic Competency. Question items of Education Unit Level Curriculum 13 both were suitable to the Bloom Taxonomy revision. It consisted of cognitive process dimension in the LOTS, MOTS, and HOTS level. The conclusion of this research was the Arabic language test for Madrasah Aliyah was considered good if it met all levels in the revised Bloom Taxonomy perspective. The researchers suggested to the classifier of the items of the Arabic language test questions in the school level that they should keep the three language elements and the four language skills in the content of the items in sufficient distribution.